Application of Statutes of Limitations to Islamic Banking: The Case of Malaysia - Muneeza, A.; Mustapha, Z. (Universiti Sains Islam Malaysia, 2024)
Limitations of action designate extent of time after an event, as set by statutes of limitations, within which legal action can be initiated by a party to a transaction. No event is actionable outside the designated time as same is rendered statute-barred. This study aims to provide an insight into application and significance of Limitations Act 1950 and Limitation Ordinance 1952 to Islamic banking matters in Malaysia as well as Shariah viewpoint on the issue of limitation of action. In conducting the study, a qualitative research methodology is employed where reported Islamic banking cases from 1983 to 2018 in Malaysia were reviewed and analysed to ascertain the application of those statutes of limitations to Islamic banking. Likewise, relevant provisions of the statutes as invoked in the cases were examined to determine possible legislative conflicts between the provisions and the rule of Islamic law in governing the right and limitation of action in Islamic banking cases under the law. The reviewed cases show the extent to which statutes of limitations were invoked in Malaysian courts in determining validity of Islamic banking matters. The limitation provisions so referred to are largely sections 6(1)(a) and 21(1) Limitations Act 1953 and section 19 Limitation Ordinance 1953, which do not conflict with Shariah viewpoint on the matter. This study will prove invaluable to financial institutions and their customers alike in promoting knowledge and creating awareness over actionable event in the course of their transactions.